HUBUNGAN PENGETAHUAN DAN SIKAP MAHASISWI DENGAN SADARI DALAM UPAYA DETEKSI DINI KANKER PAYUDARA DI PRODI S1 ILMU KEPERAWATAN UNIVERSITAS PUTRA ABADI LANGKAT - Siskawati Amri (KOLONI, 2022)
The conscious technique is very easy to do, but many women, especially teenagers, do not know this method and there are still many teenagers who do not care about and are sensitive to abnormal symptoms in their breasts. At the age of 20 a woman is recommended to do a breast self-examination every month or every three months to be able to detect early if there are abnormalities and immediately get the right treatment. One group that has reached that age is female students. The type of research used in this study was an analytic observational study with a cross-sectional study approach to the relationship between knowledge and attitudes of female students with awareness in efforts to detect early breast cancer in the undergraduate nursing program at Putra Abadi Langkat University in 2022. The sample used in this study was a total sampling of 45 people. The results showed that there was a significant relationship between female students' knowledge and awareness in efforts to detect early breast cancer in the Bachelor of Nursing study program at Putra Abadi Langkat University in 2022 obtained by calculating the chi square statistical test that p.value = 0.000 <0.05. The results showed that there was a significant relationship between female students' attitudes and awareness in efforts to detect early breast cancer in the Bachelor of Nursing study program at Putra Abadi Langkat University in 2022 obtained by calculating the chi square statistical test that p.value = 0.000 <0.05. It is expected that female students will do awareness which is useful for knowing and seeing abnormal masses in the breast, this is very important for early detection and so that female students can avoid breast cancer. Keywords: Knowledge, Attitude, The conscious technique